Temozolomide-induced liver damage. A case report - Becker, F.; Hecht, Markus; Schmidtner, J.; Semrau, S.; Fietkau, Rainer (Strahlentherapie und Onkologie, 2014)
Temozolomide (TMZ) is an alkylating agent used in chemoradiotherapy and adjuvant chemotherapy regimens for treatment of newly diagnosed or recurrent glioblastoma. In Germany alone, 900,000 daily doses of the drug are prescribed each year. Therefore, all severe side effects of TMZ, even those rarely observed, are relevant to radiotherapists.We report a case of severe drug-induced toxic hepatitis that developed during chemoradiotherapy with TMZ in a patient with glioblastoma multiforme.Transaminase elevation was observed after 5 weeks of TMZ treatment, followed by severe jaundice symptoms which only subsided 2 months later. These findings were consistent with diagnosis of the mixed hepatic/cholestatic type of drug-induced toxic hepatitis. Due to the early termination of treatment, no life-threatening complications occurred in our patient. However, rare reports of encephalopathy and fatality as complications of TMZ therapy can be found in the literature.When using TMZ for treatment of glioblastoma, monitoring of liver enzyme levels should be performed twice weekly to prevent fatal toxic hepatitis. In the case of any drug-induced hepatitis, TMZ must be discontinued immediately.
EVALuna2:18198